Water - Inoue, Takehiko (San Francisco VIZ Media, 2008)
"The artwork collected in this volume comes from TakehikoInoue's manga series Vagabond, a fictional account of the legendary samurai Miyamoto Musashi."
To be read from right to left.
Keywords: Inoue, Takehiko; Miyamoto, Musashi -- 1584-1645 -- Comic books, strips, etc; Samurai -- Japan -- Comic books, strips, etc; Figure painting -- Japan; Caricatures and cartoons -- Japan; Watercolor painting -- Japan